Emotional Rationality and Entrepreneurial Narratives: An NLP-Based Framework for Detecting Persuasive vs. Substantive Innovation Discourse - Zafar, Zia Ul Rehman; Saif, Muhammad; Hassan, Ahmad; Sultan, Ahad (University of Muhammadiyah Malang, 2026)
Entrepreneurship is increasingly recognized as a narrative-driven process; however, existing research fails to distinguish between emotionally persuasive and substantively grounded innovation discourse. This study addresses this gap by proposing the Entrepreneurial Narrative Authenticity Index (ENAI), an NLP-based metric integrating sentiment, emotion, buzzword density, technical specificity, and narrative complexity. Using a mixed-method design, we analyze 30 founder interviews (early, mid, and pro-level) and 50,000 entrepreneurship-related news articles (2023-2025). Regression results show that technical specificity (β = 0.56, p < 0.001) positively predicts innovation authenticity, while buzzword density (β = -0.43, p < 0.001) and emotional intensity (β = -0.31, p < 0.001) negatively affect it. Early-stage founders exhibit significantly higher emotional rationality scores, whereas pro-level founders demonstrate higher ENAI values. The study introduces the Emotional Rationality Lifecycle, providing a novel framework for distinguishing persuasive versus substantive innovation narratives, with implications for entrepreneurs, investors, and policy evaluation.